Computational Estimation of Some New Diarylsulfonylurea Chalcone Hybrids as Potential Cytotoxic Agents by Using Molecular Docking Studies - Akkulu Naidu, M (International Journal of Pharmaceutical & Biological Archive, 2014)
Computational Estimation of Some New Diarylsulfonylurea Chalcone Hybrids as Potential Cytotoxic Agents by Using Molecular Docking Studies